Post a New Question

Math

posted by on .

Solve and please explain how you arrived at your ans: square of 3x-1=2

  • Math - ,

    are you asking to solve for (3x -1 ) squared= 2 ?

  • Math - ,

    if so then just use foil or box technique to multiply (3x -1) against itself to get

    9x^2 -6x +1 = 2

    subtract 2 from both side to get

    9x^2 - 6x -1 = 0

    and then use quadratic formula to solve for x because i don't think you can factor this unless missing something

  • Math - ,

    or, with less work,

    (3x-1)^2 = 2
    3x-1 = ±√2
    3x = 1±√2
    x = (1±√2)/3

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question